Biting rates and developmental substrates for biting midges (Diptera: Ceratopogonidae) in Iquitos, Peru - Mercer, David R. (2003)
Biting midges (Diptera: Ceratopogonidae) were collected at 16 periurban and rural sites around Iquitos, Peru, between 17 October 1996 and 26 May 1997. Culicoides paraensis (Goeldi), the principal vector of Oropouche virus, was the most commonly collected species (9,086 flies) with Culicoides insinuatus Wirth & Blanton second (7,229 flies). Although both species were collected at all sampling sites (linear distance surveyed ≈25 km), C. paraensis dominated at northern collection sites (>90%), whereas C. insinuatus prevailed at southern collection sites (>60%). C. paraensis were collected from human sentinels at a constant rate throughout daylight hours, at similar rates during wet and dry months, and regardless of rainfall. Larval developmental substrates for C. paraensis included decaying platano (Musa X paradisiaca L. [Musaceae]) stems, stumps, flowers, fruits, and debris beneath platano trees as well as from soil beneath a fruiting mamay (Syzygium malaccense Merr. & Perry [Myrtaceae]) tree and organic-rich mud along a lake shoreline. C. insinuatus adults likewise emerged from decaying platano and organic-rich mud along a lake shoreline, but also from debris accumulated in the axils of aguaje (Mauritia flexuosa L. [Palmae]) fronds and decaying citrus fruit. Despite high numbers of biting adults near putative substrates, adults of neither species emerged from other decomposing plant material, soil, phytotelmata, or artificial containers. Because both species of biting midges emerged in high numbers from all parts of platano (ubiquitous in Iquitos), it will be challenging to control them through sanitation.